The effectiveness of working memory training on Iranian students’ academic performance: a systematic review and meta-analysis - Mahdavi, Abed; Hejazi, Elaheh; Saviz, Marzieh; Heidari, Yaser; Ghoraeian, Hoda (Frontiers in Education, 2025)
IntroductionIn the past several years, increasing interest has been in working memory training as a cognitive intervention to improve students’ academic performance. Despite the considerable interest in this topic, empirical support for the real efficacy of such interventions has been mixed and sometimes contradictory. This meta-analysis seeks to provide a systematic, evidence-based review of the functional effectiveness of working memory training.MethodsFor this purpose, we systematically searched all existing pertinent randomized controlled trials. The search was carried out both in major international academic databases, such as ScienceDirect, Elsevier, Wiley, Springer, Taylor & Francis, Scopus, PubMed, and Google Scholar, and reliable national databases, such as IranDoc, MagIran, SID, Noormags, and Civilica. This research produced 20 qualifying studies with 628 subjects.ResultsThe findings manifested a high heterogeneity among the studies and an indication of publication bias. The overall effect size of the impact of working memory training on academic performance was computed as g=1.01 (95% CI [0.05, 1.98]), indicating a statistically significant effect. However, the observed heterogeneity and possible bias in different studies render the interpretation difficult and cast doubt on the external validity of the findings.DiscussionThese results highlight the necessity for additional research employing more rigorous and better-controlled methodologies to more effectively establish the efficacy of working memory interventions in school settings.